Location Planning of Airport Facilities: Case Study of KXP International Airport - Abdul Hanan, Suhaila; Osman, Nor Hasni; Abidin, Rahimi; Mohd Zahari, Fadhilah (2022)
The selection of an airport site necessitates the consideration of several criteria constrained by complex trade-offs. In terms of influencing factors and multicriteria assessment methods, airport literature and practise provide valuable insights. This paper discussed the factors that were considered when deciding where to build a new airport in Kulim, Malaysia. Interviews and secondary data collection have taken place. According to the findings, some of the criteria for location decisions include land size and shape, topography, social and environmental impact, and transportation network.